TMEM88 Modulates Lipid Synthesis and Metabolism Cytokine by Regulating Wnt/β-Catenin Signaling Pathway in Non-Alcoholic Fatty Liver Disease - Zhou, Huan; Zhu, Xingyu; Yao, Yan; Su, Yue; Xie, Jing; Zhu, Minhui; He, Cuixia; Ding, Jiaxiang; Xu, Yuanyuan; Shan, Rongfang; Wang, Ying; Zhao, Xiangdi; et al. (Frontiers in Pharmacology, 2022)
Abstract Objective: To clarify the molecular mechanism of TMEM88 regulating lipid synthesis and metabolism cytokine in NAFLD. Methods: In vivo, NAFLD model mice were fed by a high-fat diet (MCD). H&E staining and immunohistochemistry experiments were used to analyze the mice's liver tissue. RT-qPCR and Western blotting were used to detect the lipid synthesis and metabolism cytokine. In vitro, after stimulating AML-12 cells with fatty acids (FFA), pEGFP-C1-TMEM88 and TMEM88 siRNA were transfected in cells respectively, and the expression level of SREBP-1c, PPAR-α, FASN, and ACOX-1 were evaluated by RT-qPCR and Western blotting. Results: The study found that the secretion of PPAR-α and its downstream target ACOX-1 were up-regulated, and the secretion of SREBP-1c and its downstream target FASN were reduced after transfecting with pEGFP-C1-TMEM88. But when TMEM88 was inhibited, the experimental results were opposite to the above conclusions. The data suggested that it may be related to the occurrence, development and end of NAFLD. Additionally, the study proved that the Wnt/β-catenin signaling pathway was activated by TMEM88siRNA. TMEM88 can accelerate the cell-death rate of AML-12 cells induced by FFA activating Wnt/β-catenin signaling pathway. Conclusion: Overall, the study proved that TMEM88 takes part in regulating the secretion of lipid synthesis and metabolism cytokine (SREBP-1c, PPAR-α, FASN and ACOX-1) through the Wnt/β-catenin signaling pathway in AML-12 cells.